Mortality Benefit of Remdesivir in COVID-19: A Systematic Review and Meta-Analysis - Bansal, Vikas; Mahapure, Kiran S.; Bhurwal, Abhishek; Gupta, Ishita; Hassanain, Sahar; Makadia, Janaki; Madas, Nimisha; Armaly, Paige; Singh, Romil; Mehra, Ishita; O'Horo, John C.; Kashyap, Rahul (Frontiers in Medicine, 2021)
Importance/Background: During current public health emergency of COVID-19 pandemic, repurposing of existing antiviral drugs may be an efficient strategy since there is no proven effective treatment. Remdesivir has demonstrated broad spectrum antiviral activity against an array of RNA virus families and has been recently recognized as a promising therapy against SARS-CoV-2. Methods: A systematic search was conducted for full length manuscripts published between inception and July 19th, 2020 focussing on efficacy and safety of Remdesivir in COVID-19. The primary outcomes were defined as mortality rate and median days to recovery based on the available pooled data. The secondary outcome was adverse events rate and drug discontinuation rate. Statistical analysis: All outcomes were performed using Comprehensive Meta-Analysis software package (Bio stat, Englewood, NJ, USA). Results: A total of 1895 patients from 9 studies were included in this qualitative synthesis. In patients treated with Remdesivir, the mean recovery time was 15.84 days (95% CI 11.68-20, SE 2.12; I2=97.24) and the pooled mortality rate was 11.3% (95% CI 7.9%- 16%; I2= 74.85). However, treatment with Remdesivir was associated with adverse effects (55.3%, 95% CI 31.5%- 76.9%; p=xx; I2=97.66) eventually warranting the discontinuation of the drug (17.8%, 95% CI 8.6%- 33.1%; I2=95.64). The meta-analysis of three clinical trials indicated that administration of Remdesivir significantly reduces the mortality compared to the placebo (OR 0.70, 95% CI 0.58-0.84, p=<0.001; I2=16.6). Conclusions and Relevance: The result of contemporary meta-analysis suggests that pooled mortality rate with Remdesivir was low and median recovery time was over 2 weeks.